Ecological sanitation as a way of improving the soil-vegetation cover - Ремез, Н. С.; Бойко, А. Г. (Science-based technologies, 2018)
This article is about the problem of degradation of soil-vegetation cover due to the depletion of soil by careless farming of mankind. This determines to implementation of steps to solve problems in this area, because the chosen field of activity relates to the priority needs of the population in food, which reveals the relevance of the chosen topic. The one of the ways to improve soil-vegetation cover through the use of ecological sanitation highlights in the work. The ecological sanitation, first of all, can improve the environmental indicators of some necessary resources for our lives, in particular the closed cycle of waste of human life, which introduces by this technology, helps to reduce water pollution. The emphasis is the content of nutrients in organic fertilizers, which obtained as a result of ecological sanitation use. This knowledge is necessary for applying fertilizers to the soil, this is predetermines the practical use of the research.